2003
DOI: 10.1152/ajprenal.00383.2002
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone regulation of glomerular AT1angiotensin receptors in adult uninephrectomized male rats

Abstract: roney. Growth hormone regulation of glomerular AT1 angiotensin receptors in adult uninephrectomized male rats. Am J Physiol Renal Physiol 285: F1085-F1091, 2003. First published June 24, 2003 10.1152/ajprenal.00383.2002.-Sex differences exist in the mechanisms initiating early compensatory renal growth after unilateral nephrectomy (UNX); remnant kidney growth is growth hormone (GH) independent in adult female rats and GH dependent in adult male rats. The present study determined whether sex differences also e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 35 publications
1
18
0
1
Order By: Relevance
“…These findings are consistent with our previous studies that showed RNA-protein complex formation in the AT 1a R 5ЈLS is regulated in a manner that inversely correlates with changes in AT 1 R densities under a variety of conditions, including dietary sodium manipulation (16), estrogen deficiency (33), and renal mass ablation (22).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are consistent with our previous studies that showed RNA-protein complex formation in the AT 1a R 5ЈLS is regulated in a manner that inversely correlates with changes in AT 1 R densities under a variety of conditions, including dietary sodium manipulation (16), estrogen deficiency (33), and renal mass ablation (22).…”
Section: Discussionsupporting
confidence: 93%
“…Under these experimental conditions, there were no significant differences in the degree of receptor internalization in RMICs cultured under isoosmotic or hyperosmotic conditions [endocytosis rate constant (min Effect of osmolality on AT 1 R RNA-protein complex formation in RMICs. We have previously shown that alterations in the levels of cytosolic proteins, which bind to the 5ЈLS of the AT 1a R are associated with inverse changes in AT 1a R protein expression (15,16,22). To determine whether osmolality alters the levels of RNA-protein complex (RPC) formation in the 5ЈLS in RMICs, we performed RNA EMSAs with radiolabeled 5ЈLS on cytosolic extracts prepared from RMICs cultured under isoosmotic and hyperosmotic conditions (Fig.…”
Section: No Significant Differences In the Percentage Of Nonviable Cementioning
confidence: 99%
“…Alternatively, recent work implicates growth hormone (GH) in sex-dependent differences in renal expression of glomerular AT 1 during hypertrophy following uninephrectomy; male rat kidneys show increased glomerular AT 1 expression, whereas females do not (86). Because there is sexual dimorphism in GH release these observations may hold implications for both normal and pathological growth and development of the kidney.…”
Section: Potential Mechanisms Underlying Sex Differences In Developmementioning
confidence: 99%
“…Taken together, it appears that the influence of sex on the developmental origins of disease may reach far beyond the widely recognized role of sex hormones. Alternatively, recent work implicates growth hormone (GH) in sex dependent differences in renal expression of glomerular AT 1 during hypertrophy following uninephrectomy; male rat kidneys show increased glomerular AT 1 expression, whereas females do not (Mok et al, 2003). Because there is sexual dimorphism in GH release these observations may hold implications for both normal and pathological growth and development of the kidney.…”
Section: Sex Steroidsmentioning
confidence: 99%